TeX source:
\begin{array}{rclcl} \dfrac{1}{2}\left(x-\dfrac{3}{2}\right)^2-\dfrac{25}{4} &=& 0 \cr & ...& \cr \dfrac{1}{2}x^2-\dfrac{3}{2}x+2 &=& 0 &\vert& \cdot 2 \cr x^2-3x-4 &=& 0 &\vert& \text{p-q-Formel} \cr x_{1,2} &=& -\dfrac{-3}{2} \pm \sqrt{\left(\dfrac{-3}{2} \right)^2-\left(-4\right)} \cr\cr x_{1,2} &=& \dfrac{3}{2} \pm \sqrt{\dfrac{9}{4}+4} \cr\cr x_{1,2} &=& \dfrac{3}{2} \pm \sqrt{\dfrac{25}{4}} \cr\cr x_1 &=& \dfrac{3}{2}+\dfrac{5}{2} = \dfrac{8}{2} = 4 \cr\cr x_2 &=& \dfrac{3}{2} -\dfrac{5}{2} = -\dfrac{2}{2} = -1 \end{array}